Characterizing anomalies in distributed strain measurements of cast-in-situ bored piles - Mohamad, H. (Penerbit UTM Press, 2016)
This paper describes the method of identifying typical defects of bored cast-in-situ piles when instrumenting using Distributed Optical Fiber Strain Sensing (DOFSS). The DOFSS technology is based on Brillouin Optical Time Domain Analyses (BOTDA), which has the advantage of recording continuous strain profile as opposed to the conventional discrete based sensors such as Vibrating Wire strain gauges. In pile instrumentation particularly, obtaining distributed strain profile is important when analysing the load-transfer and shaft friction of a pile, as well as detecting any anomalies in the strain regime. Features such as defective pile shaft necking, discontinuity of concrete, intrusion of foreign matter and improper toe formation due to contamination of concrete at base with soil particles, among others, may cause the pile to fail. In this study, a new technique of detecting such defects is proposed using DOFSS technology which can potentially supplement the existing non-destructive test (NDT) methods. Discussion on the performance of instrumented piles by means of maintained load test are also presented. Â© 2016 Penerbit UTM Press. All rights reserved.